A review of recommendations for medical undergraduate intellectual disability psychiatry teaching from UK reports. Issue 2 (7th March 2016) - Spackman, Ross; Qureshi, Adnan; Rai, Dheeraj
Abstract : Purpose: – The purpose of this paper is to amalgamate recommendations from contemporary national reports on healthcare provision and needs of people with intellectual disabilities. The paper combines these with recommendations for undergraduate curricula of medical students from the GMC and Royal College of Psychiatrists (RCPsych). Design/methodology/approach: – National reports from Mencap, Department of Health, Disability rights commission, NHS Executive, the GMC and RCPsych were searched for relevant recommendations to undergraduate medical education in ID psychiatry. Recommendations were collated and grouped to form a single list for use when planning future curricula or auditing existing teaching. Findings: – In total, 13 relevant recommendations were identified in nine groups. These included that people with intellectual disabilities and their carers should be involved in the teaching. That teaching should include the ethical, moral and legal obligations and should include the mental capacity act and equality act. Institutional and individual discrimination should be highlighted as a problem and diagnostic overshadowing should be covered. Originality/value: – This paper has collated in a single document the combined recommendations of multiple reports. These are relevant to medical undergraduate teaching and may also be of use to other undergraduate healthcare courses. They are a useful template for others wishing to examine or benchmark the content of their medical undergraduate ID psychiatry teaching against an amalgamated list.